The three pillars of stability: legitimation, repression, and co-optation in autocratic regimes - Johannes Gerschewski (Democratization, 2013)
Why do some autocracies remain stable while others collapse? This article presents a theoretical framework that seeks to explain the longevity of autocracies by referring to three pillars of stability: legitimation, repression, and co-optation. These three causal factors are derived by distilling and synthesizing the main arguments of classic and more recent research efforts. Particular emphasis is paid to re-incorporate legitimation in the explanation of stable autocracies. The article conceptionalizes the three pillars and discusses methods of concrete measurement. It then moves on to explain the stabilization process. How do these pillars develop their stabilizing effect? It is argued that reinforcement processes take place both within and between the pillars. They take the form of exogenous reinforcement, self-reinforcement, and reciprocal reinforcement. To illustrate the inner logic of these processes, I draw on empirical examples. I also state what we would need to observe empirically and how we can approach the three pillars methodically. A theoretical framework of this nature has two advantages: it is able to take the complexity of autocratic regimes into account while remaining parsimonious enough to be applicable to all autocratic regimes, irrespective of their subtype; and it integrates a static view to explain stability, with the emphasis on the underlying stabilization mechanisms and facilitates within-case and cross-case comparisons.
Keywords: 330; autocracy; stability; legitimation; repression; co-optation